Deskripsi Implementasi Kurikulum Merdeka di TK Negeri Mekar Suwawa - Ananda Tasya Isami; Sri Ramlawati Monoarfa; Virgina Cahyani; Nazwa Fathlyah Makmur; Pupung Puspa Ardini; Sri Rawanti (Inovasi Pendidikan dan Anak Usia Dini, 2025)
brings various challenges as well as opportunities in efforts to improve the quality of early The implementation of the Independent Curriculum in Early Childhood Education (PAUD) childhood education in Indonesia. This article discusses the views of teachers regarding the implementation of the Independent Curriculum, highlighting aspects of understanding, implementation, and impact. Based on the results of the questionnaire and in-depth analysis, it is known that most teachers have understood the Independent Curriculum quite well, although more optimal training and mentoring are still needed. Obstacles faced in its implementation include limited facilities and infrastructure, lack of support from management, and challenges in adapting new learning approaches. Even so, the Independent Curriculum has been proven to have a positive influence on children's enthusiasm for learning and increase parental participation in the education process. In conclusion, with the cooperation and commitment of various parties to continue to improve the quality of PAUD, the Independent Curriculum has great potential to provide innovation and maximum benefits for the growth and development of children in Indonesia.